Gender Household Survey - CGIAR Research Program on Climate Change, Agriculture and Food Security; International Food Policy Research Institute; International Livestock Research Institute (2013)
The purpose of this survey is to gather gender-disaggregated data on agricultural activities, decision-making, weather information, risk-perception and values from rural households in Kenya, Bangladesh, Uganda and Senegal. The survey ultimately will cover 200 households in each site - the same households that were sampled for the IMPACT Lite Surveys. This survey builds on the information collected in that round, supplementing the detailed productivity related information with data on decision-making and other topics. This information will be used for researchers, policy-makers and development practitioners to better understand the vulnerabilities of men and women to climate change, how they differ, and what actions can be taken to reduce that vulnerability.